Unveiling the profound influence of sucralose on metabolism and its role in shaping obesity trends - Singh S, Ankul; Singh, Srishti; Begum, Rukaiah Fatma; Vijayan, Sukanya; Vellapandian, Chitra (Frontiers in Nutrition, 2024)
Artificial sweeteners, prominently exemplified by sucralose, have become pervasive in contemporary diets, prompting intriguing questions about their impact on metabolism and their potential role in the unfolding trends of obesity. Covering topics from its discovery to analytical methods for detection and determination in food samples, the manuscript scrutinizes the metabolic effects of sucralose. Notably, the association between sucralose intake and obesity is examined, challenging the conventional belief of its role in weight management. The document comprehensively examines in vivo studies, revealing sucralose's implications on insulin resistance, gut microbiota, and metabolic syndrome, providing a nuanced comprehension of its impact on human health. Additionally, it explores sucralose's effects on glucose and lipid metabolism, blood pressure, and cardiovascular health, underscoring its possible involvement in malignancy development. The review concludes with a call for increased public awareness, education, and updated dietary guidelines to help individuals make informed choices about sweetener consumption. The future perspectives section highlights the need for longitudinal studies, exploring alternative sweeteners, and refining acceptable daily intake limits to ensure public health recommendations align with evolving regulatory guidelines. Overall, the manuscript provides a comprehensive overview of sucralose's multifaceted impact on health, urging further research and a balanced perspective on sweetener consumption.